Development of 2D Animation Videos as English Learning Media - Khusnatul Amaliah; Hastuti Retno Kuspiyah; Somia Ela Safrika (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2023)
Multimedia is a complete tool that is effective in the teaching and learning process in the era of the industrial revolution 4.0. Coupled with the existence of elements supporting the success of the learning process, namely learning methods and learning media. Learning development is one of the Higher Order Thinking Skills (HOTS) as a reinforcement of character education and learning in the face of the industrial revolution era 4.0. Educators must prepare their students to be able to face the era of disruption by strengthening new literacy skills, namely data, technology and humanism. So that educators are required to innovate to communicate and convey messages to learners.